Typology and effects of co-opetition in buyer-supplier relationships: Evidence from the chinese home appliance industry - Liu, Y.; Luo, Yadong; Yang, P.; Maksimov, V. (2014)
Building on the co-opetition perspective, this study takes a unified approach to examine relationship benefits and transaction costs in buyer-supplier relationships. We argue that buyer-supplier vertical dyads fall into one of four distinct co-opetition types based on their respective degrees of cooperation and competition. Each co-opetition situation then corresponds to unique levels of relationship benefits and transaction costs. A sample of 225 supplier-buyer dyads from the Chinese home appliance industry confirms that competition has a positive effect on transaction costs and a negative effect on relationship benefits, while cooperation stimulates greater relationship benefits but affects transaction costs mainly at low competition levels. The results advance prior research on buyer-supplier relationships and co-opetition and offer valuable avenues for future research.